Study Of Processing Parameters In Manufacturing Of Flat Glass-Epoxy Composite Laminates Using Vacuum Bagging Oven Curing - Hanafiah, Nur Hafzareen Md (2013)
The effective manufacturing process for aircraft structural parts made from composite laminate usually involved autoclave prepreg material manufactured via vacuum bagging pre-forming and autoclave. Though, autoclave involves high capital, running cost and extortionate residual stress. Vacuum bagging only (VBO) pre-forming process with oven curing is the closest out-of-autoclave (OoA) method shifts from autoclave. Thus, this study focuses on the vacuum bagging pre-forming process in oven cure using the autoclave. This work involved revising the design of experiment (DOE) to design the possible experiments to be conducted in a systematic approach. The effects of vacuum bagging process of layup technique (debulking) and vacuum bagging configurations (edge breather, intensifier and mould release type) towards void content and mechanical properties of laminate produced were investigated using analysis of variance (ANOVA). The physical quality analysis is also performed to evaluate the thickness variation and abnormalities throughout the laminate. The abnormalities percentage of the produced laminate was studied using the image processing algorithm of ultrasonic C-scan image. To assess the relationship between void and inter-laminar shear strength (ILSS), scanning electron micrograph analysis was employed. It was concluded that the ILSS and tensile strength were reflected directly to the void content and void dimension which were also sensitive to the processing parameters.